Cross sections and thick target yields of (d,xn) reactions on natural lead - Wasilevsky, C.; Vega Vedoya, M. de la; Nassiff, S. J. (1980)
Fil: Wasilevsky, C. Comisión Nacional de Energía Atómica; Argentina